Wheat Apoplast-Localized Lipid Transfer Protein TaLTP3 Enhances Defense Responses Against Puccinia triticina - Zhao, Jiaojie; Bi, Weishuai; Zhao, Shuqing; Su, Jun; Li, Mengyu; Ma, Lisong; Yu, Xiumei; Wang, Xiaodong (Frontiers in Plant Science, 2021)
Plant apoplast serves as the frontier battlefield of plant defense in response to different types of pathogens. Many pathogenesis-related (PR) proteins are accumulated in apoplastic space during the onset of plant–pathogen interaction, where they act to suppress pathogen infection. In this study, we found the expression of Triticum aestivum lipid transfer protein 3 (TaLTP3) gene was unregulated during incompatible interaction mediated by leaf rust resistance genes Lr39/41 at the early infection stage. Stable transgenic wheat lines overexpressing TaLTP3 exhibited enhanced resistance to leaf rust pathogen Puccinia triticina. Transcriptome analysis revealed that overexpression of TaLTP3 specifically activated the transcription of pathogenesis-related protein 1a (TaPR1a) and multiple plant hormone pathways, including salicylic acid (SA), jasmonic acid (JA), and auxin, in response to the infection of the model bacterial pathogen Pseudomonas syringae pv. tomato DC3000. Further investigation indicated that TaLTP3 physically associated with wheat TaPR1a protein in the apoplast. Transgenic wheat lines overexpressing TaLTP3 and TaPR1a showed higher accumulations of reactive oxygen species (ROS) during plant defense responses. All these findings suggested that TaLTP3 is involved in wheat resistance against leaf rust pathogen infection and forming a TaLTP3-TaPR1a complex in apoplast against this pathogen, which provides new insights into the functional roles of PR proteins.